Velasco and commemoration policies sesquicentennial in Peru - Chaupis Torres, José (2022)
The celebration for the 150 years of the independence of Peru was an exceptional juncture for Velasco to promote his cultural policy, carrying out an intense revisionist activity to rewrite history, resignifying in memory the sense of independence, promoting the State through its institutions a unique official imaginary, to justify their actions defining identities in the present to achieve a desired future, at a juncture of historiographic turn where traditional history - whose representatives would make up the National Commission of the Sesquicentennial of the Independence of Peru (CNSIP) - was being questioned by the emerging New History. The article will be organized in three sections, in the first, the cultural policy of Velasquismo will be studied based on its constitutive elements, which tried to institutionally legitimize the military government. In the second, the structure of the celebrations will be studied, which would articulate the memory recreated by the military in the commemoration and the history investigated by the historians of the CNSIP on what was commemorated. In the third, we will analyze the debate between the officials of the regime, members of the CNSIP, the teachers› union and the historians of the New History fighting for the meaning of the past.